Electrical System Design for High Rise Building Based on Reliability Index - Juhan Andi Praseto Aji; Bambang Suprianto; Unit Three Kartini (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
The research discusses the evaluation of electrical systems in multi-storey buildings, including analysis of compliance with PUIL 2011 standards and integration of Faraday Cage-based lightning protection systems. This study focuses on the Pasar Baru Bandung Building, with the aim of assessing the efficiency and safety of the electrical system used. The research method is carried out through the stages of field observation, data collection, and data processing. Observations were made to identify electrical equipment and assess the feasibility of its use. Data collection includes load capacity and single line diagrams, which are then processed to determine the value of Strong Current Conductivity (KHA) and Drop Voltage. The results of data processing were compared with existing data and analysed based on applicable standards. The results show that the power distribution system in Pasar Baru Bandung Building has been designed with high efficiency, with organised power distribution through main panels and sub-panels. The electrical protection evaluation shows that the grounding and earthing system has met the safety standards to prevent electrical faults. In addition, lightning protection analysis with the Rolling Sphere method ensures that the building's protection against lightning strikes is at an optimal level. The benefit of this study is the comprehensive examination of the electrical system, considering power distribution, protection, and energy efficiency. Despite challenges like inaccuracies in voltage drop measurement due to factors like environmental conditions and equipment age, the research still has a significant impact on improving the safety and efficiency of electrical systems in tall buildings.